22.4k views
3 votes
4x + y = 8

6y- 9y = 12
Which of the options represents the resulting equation after an equivalent expression for y is substituted into the second equation?
4x + 4x - 8 = 8
6(4x - 8) - 9y = 12
6x - 9(-4x + 8) = 12

1 Answer

4 votes

Answer:

6x - 9(-4x + 8) = 12

Explanation:

Solving the first eqution for y, you have

... y = -4x +8

Substituting that into the equation

... 6x -9y = 12

you have ...

... 6x -9(-4x +8) = 12 . . . . . . . matches the 3rd choice.

_____

Comment on the question

The given equation is 6y -9y = 12, something entirely different from 6x -9y = 12. None of the answer choices apply to the equations given in your problem statement.

User Raysa
by
5.7k points